(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes the development of tourism in Uzbekistan and its impact on the economy. The research examines tourism reforms, the importance of historical and cultural heritage sites, infrastructure development, and the contribution of tourism to economic growth. The article highlights the role of tourism in increasing employment, supporting small businesses, accelerating regional development, and strengthening the international image of the country. In addition, the study discusses existing challenges in the tourism sector and identifies future opportunities for sustainable tourism development.